Educational program on oral health aimed at families with preschool children residing in the Balboa Neighborhood - Nancy Díaz Canedo; Yanisleydi Morales Cruz; Maricelys de la Caridad Hernández Cabeza; Yety Isabel Rosado Fernández; Gilberto Salas Contreras; Yainí Frenes Pérez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
Background: health promotion should begin at an early age of development, so that children acquire healthy lifestyles that will be beneficial in the future. Objective: to implement an educational oral health program, aimed at the families of children from three to five years old enrolled in the Educate your child Program, from clinics eight and nine of the Ramón Balboa neighborhood, in Lajas municipality. Methods: an intervention study was carried out, from September 2020 to July 2021, at the headquarters of the Educate your child program, with 35 family members and 35 children between three and five years old enrolled in this program. The analyzed variables were: knowledge about oral hygiene, dietary habits and deforming habits, measured before and after the educational intervention. Results: the female sex and age of four years prevailed. The relatives were between 20 and 34 years old. The main risk factors identified were poor oral hygiene, incorrect tooth brushing and cariogenic diet. Before the intervention, regular knowledge about oral hygiene, poor knowledge about dietary habits, and a poor level of knowledge about deforming habits prevailed. After the intervention, a higher percentage of good knowledge about oral hygiene, dietary habits and a good level of knowledge about deforming habits was observed. Conclusions: after applying the educational intervention, a notable improvement in knowledge about oral health was evidenced.